Forecasting Atmospheric Visibility over the Summer North Atlantic Using the Principal Discriminant Method. - Elias,K. C. (1985)
This thesis describes the application and evaluation of the Principal Discriminant Method (PDM) in the forecasting of horizontal visibility over selected physically homogeneous areas of the North Atlantic Ocean. The main focus is to propose a possible model output statistics (MOS) approach to operationally forecast visibility at the 00-hour model initialization time and the 24-hour and 48-hour model forecast projections, using as data the period 15 May--7 July 1983. The technique involves the manipulation of observed visibility and the Fleet Numerical Oceanography Center's Navy Operational Global Atmospheric System (NOGAPS) model output parameters. Both two-and three-category visibility models were examined. The resulting zero-and one-class errors as well as the threat scores from the PDM model were compared with those obtained from maximum probability and natural regression studies. For the majority of the experiments performed, PDM was outperformed by the other techniques, although one trail run of an adjusted PDM technique gave results similar to those of the maximum probability techniques. Keywords: Marine visibility; Visibility forecasting; Categorical forecasting.